Legal Dynamics Against E-Commerce Couriers Who Commit Default on the COD System - Wardhono, Agus; Syahmi, Taffy Faiq; Prawesthi, Wahyu (Dinasti Research, 2025)
The growth of e-commerce in Indonesia has given birth to new innovations, namely Cash On Delivery (COD) which is currently popular, but still causes various problems. This study aims to analyze the status of couriers as intermediaries between buyers and sellers in online transactions with the COD system, as well as their legal responsibilities when a default occurs. Using a normative legal research method, this study examines that couriers operate under the legal umbrella of Article 1800 of the Civil Code as parties exercising power on behalf of the shipping service company, which previously received power from the seller (Article 1792 of the Civil Code). The legal relationship between the seller and the courier is an agency relationship where the seller is the principal and the courier is the agent. COD transactions are considered valid based on Article 1458 of the Civil Code which requires an agreement on the object and price of the goods. This study reveals an inequality in legal protection for couriers, as seen in the viral case of a courier who was fined IDR 500,000 for the issue of IDR 700 change, even though he had shown good faith by trying to return the remaining money